The impact of reality television program on Universiti Teknologi Mara Terengganu’s students / Nor Syamaliah Ngah and Thenmolli Vadeveloo - Ngah, Nor Syamaliah; Vadeveloo, Thenmolli (2012)
Television has a great influence over morality of viewers, as they tend to match their own judgments of what is good and bad with the value system created by television programs. This could create moral and ethical conflicts in the viewer. As reality TV programs were perceived to be more real than other TV programs, their effect on the viewers' attitudes and values was stronger. The dramatic rise in the popularity of reality television shows at the present time can be considered as phenomenal in the world media landscape. Many reality shows have created history in terms of people’s participation and revenue generation. The aim of this paper is to find out the factors that influence the students of Universiti Teknologi MARA Terengganu to watch reality television program. This descriptive research used 361 students from 12 programs as a sample. The results show that most of the respondents like to watch the reality television program that is more challenging in term of physical and mental. In most cases they watch the program because it’s entertaining and give positive impact to them.